2x - 5 < - 3 + 2
3x - 2 > 2x + 4

Resoudre : 3 (2x+1) -9 = 2 (2x + 1)
(3x + 5) (2x + 13) = 0

Factoriser : (x + 3) (x - 2) + (x + 3)
(x - 1) (2x + 1) - (1+2x)(x+1)
x au carre + 12x + 36
36 x au carre - 144
9x au carre - 9

Svp aider moi !!

1

Réponses

2013-06-24T14:02:08+02:00

2x - 5 < - 3 + 2

2x<5-3+2

2x<4

x<4/2

x<2

 

3x - 2 > 2x + 4

3x-2x>2+4

x>6

 

 

3 (2x+1) -9 = 2 (2x + 1)

6x+3-9=4x+2

6x-4x=2+6

2x=8

x=8/2

x=4

 

(3x + 5) (2x + 13) = 0

3x+5=0

x=-5/3

 

2x+13=0

2x=-13

x=-13/2

 

Factoriser : (x + 3) (x - 2) + (x + 3)

(x+3)(x-2+1)=(x+3)(x-1)

 

(x - 1) (2x + 1) - (1+2x)(x+1)

(2x+1)(x-1-(x+1))=(2x+1)(x-1-x-1)=-2(2x+1)

 

x²+12x+36=(x+6)²

(x+6)²=(x+6)(x+6)

 

36x²-144=(6x)²-12²=(6x-12)(6x+12)

 

9x²-9=(3x)²-3²

(3x)²-3²=(3x-3)(3x+3